"The Sculpture Biennale of Ein Hod, 1990" : Nature Has Built Us a Museum : Sculpture in a Human Dimension - Aharonson, Meir; Sculpture Biennale Ein-Hod 1990 (Ein Hod : Sculpture Biennale Ein Hod, 1990)
Ben-David, Zadok ; Ben-Zvi, Roni ; Cohen-Caspi, Mirit ; Cohen-Levy, Maya ; Denkner, Yardena ; Dominey, Drora ; Dorchin, Yaacov ; Efrat, Benny ; Feigin, Dov ; Gilinsky, Yoel ; Gitlin, Michael ; etc.
"The Sculpture Biennale of Ein Hod, 1990" : Nature Has Built Us a Museum : Sculpture in a Human Dimension, Sculpture Biennale Ein Hod
boek